Aspectos tecnológicos e nutricionais envolvidos na germinação de grãos e produção de brotos comestíveis - Barroso, Junia Ariane Duarte (2022)
The population's interest in consuming functional foods is growing since they are considered foods rich in bioactive compounds that exert beneficial effects on health. The sprouts, originating from the germination of seeds, are rich in bioactive compounds, vitamins, minerals, and dietary fibers and have become popular on social networks as “living foods”. Given this scenario, the scientific community has been engaged, in recent years, in the investigation of the processes involved in the production of sprouts and germinated grains, requiring an updated review of technological and nutritional approaches to seed germination that have been studied. In this sense, this work contemplates the main aspects related to the production of germinated grains and edible sprouts from seed germination, addressing (i) which seeds can be germinated (ii) the methodologies that contribute to the germination and sanitization of seeds (iii) the influence of germination on the nutritional quality of shoots and (iv) the application of germinated grains in the production of functional foods. through the bibliographic review, information was compiled, regarding the nutritional aspect, thirty-three species of seeds used for the production of sprouts were characterized from cereals, pseudocereals, legumes, oilseeds and vegetables. In several studies, it was observed that germination made it possible to increase the content of important bioactive compounds in the sprouts, namely, phenolic compounds, flavonoids, ɣ-aminobutyric acid (GABA), B vitamins, as well as increasing the antioxidant capacity and reducing the antinutrients present in the seeds. Despite being considered healthy, sprouts and seeds require the practice of sanitization to ensure microbiological safety for consumers, and different emerging treatments have been shown to be efficient in eliminating pathogens. The reviewed studies reveal that sprouted grains have better health-promoting properties than their respective non-sprouted seeds and can also serve as interesting ingredients in producing foods with functional properties, adding value to processed foods.